Mechanism and kinetics analysis of valuable metals leaching from copper-cadmium slag assisted by ultrasound cavitation. (15th December 2022) - Liu, Hongliang; Wang, Shixing; Fu, Likang; Zhang, Gengwei; Zuo, Yonggang; Zhang, Libo
Abstract: Copper-cadmium slag, produced during the hydrometallurgical process of zinc, is considered as hazardous solid waste. However, a large number of valuable metals (zinc, cadmium, copper and magnesium) are contained in copper-cadmium slag. It is necessary to treat copper-cadmium slag to make it harmless and recycled with an efficient mean. In response to the problems of low oxidation and multiple inclusions hindering leaching reaction, a more effective and ecologically friendly method based on ultrasonic cavitation and mechanical effect is suggested for recovering valuable metals from copper-cadmium slag. The influencing factors of leaching experiment include reaction time, leaching temperature, liquid-solid ratio, sulfuric acid concentration and ultrasound power. The leaching rates of zinc, cadmium, copper and magnesium reached over 97% at 300 W of ultrasonic power, which are much better than that of conventional condition. In addition, ultrasonic assistance shortened the leaching time to 2 h, improving the leaching rate and reducing the extra energy consumption during conventional leaching in the metal recovery process. The particle size of copper-cadmium slag is reduced from 30 μm to 1 μm by virtue of the ultrasonic microjet and microbubble effects. Moreover, the mineralogy analysis results indicate that microstructures and composition of solid slag changed greatly after ultrasonic treatment. The kinetic analysis results show that the activation energy decreases from 34.68 kJ/mol to 6.21 kJ/mol after ultrasound, demonstrating that ultrasonic field can reduce the activation energy and accelerate the reaction rate. As a result, ultrasound-assisted method is shown to be considerably powerful in improving the leaching and recovery efficiency of solid waste slag. Graphical abstract: Image 1 Highlights: An ultrasound-assisted measure was proposed to high-efficiently recover copper-cadmium slag. Reaction mechanism is attributed to the cavitation and mechanical effects of ultrasound. The leaching rate of copper is over 97% under the optimal conditions. Ultrasound-assisted can enhance recovery rate visibly compared with traditional metallurgy.